Management Planning in Public Enterprises - Planning Commission, Government of India (Planning Commission, Government of India, 1965)
The document examines management planning in Indian public enterprises, highlighting common challenges across project development phases—pre-construction, construction, and operation. Key findings reveal that delays, cost overruns, and lower capital returns are frequently linked to inadequate management practices. Recommendations focus on adopting advanced techniques, including detailed feasibility studies, Work Breakdown Structures, PERT/CPM scheduling, and integrated operational and financial reporting systems. Emphasis is placed on developing skilled personnel through recruitment, training, and knowledge-sharing initiatives. The study underscores that efficient management is critical for maximizing returns on public investments, enhancing project outcomes, and supporting India’s broader economic and industrial development objectives.
Management Group Committee on Plan Projects
Keywords: Public Enterprises; Management Planning; Project Phases; Pre-Construction; Construction Phase; Operational Phase; Work Breakdown Structure; PERT/CPM; Financial Management; Feasibility Studies; Personnel Development; Performance Improvement